Case Report: TNFα Antagonists Are an Effective Therapy in Cardiac Sarcoidosis - Stievenart, Julien; Le Guenno, Guillaume; Ruivard, Marc; Rieu, Virginie; André, Marc; Grobost, Vincent (Frontiers in Cardiovascular Medicine, 2021)
INTRODUCTION: Cardiac sarcoidosis (CS) is a life-threatening disease in which clear recommendations are lacking. We report a case series of CS successfully treated by tumour necrosis factor (TNF)α antagonists. METHODS: We conducted a single centre retrospective study of our patients with CS treated by TNFα antagonists. RESULTS: Four cases (4/84, 4.7%) were found in our database. Mean age was 40 years (range 34–53 years) and all were Caucasian men. Mean follow-up was 54.75 months (range 25–115 months). All patients received corticosteroid therapy (CT) and immunosuppressive therapy (IT). TNFα antagonists (infliximab or adalimumab) were started after the first or second CS relapse under CT and IT. One patient experienced relapse under TNFα antagonists (isolated decreased left ventricular ejection) and responded to a shorter duration of TNFα antagonist infusion. CT was discontinued in three patients treated with TNFα antagonists without relapse or major cardiac events during follow-up. No serious adverse event occurred in our case series, possibly due to dose sparing and frequent arrest of CT. CONCLUSION: for these four patients, TNFα antagonists were effective in refractory and/or relapsing CS treated by corticosteroids and/or immunosuppressive agents, without serious adverse events.